Biochemical responses of the giant clam (Tridacna squamosa Lamarck, 1819) and the burrowing sea urchin (Echinometra mathaei (de Blainville, 1825)) to spatial and seasonal variations on the Red Sea coast of Egypt - Samaa G. El-Sokkary; Khaleid F. Abd El-Wakeil; Ahmad H. Obuid-Allah; Mohsen Y. Omer (Egyptian Journal of Aquatic Research, 2023)
This study aims to investigate the spatial and seasonal impacts on the biochemical responses of two bioindicators: Tridacna squamosa and Echinometra mathaei which inhabit the Red Sea coast of Egypt. Samples were collected from three sites during the summer of 2019 and the winter of 2020. Total protein, MDA, and enzyme activity of pyruvate kinase (PK) and lactate dehydrogenase (LDH) were measured in the gonads of the collected samples. The results confirmed that environmental variables vary at both spatial and seasonal levels, where the two species exhibited different patterns of biochemical response to internal and external stresses. In addition, both studied species did not resort to anaerobic respiration as a defense mechanism. Therefore, this study confirms that the use of biomarkers in the field shall be regarded as a general warning of internal and external stress.